Describing variation in formula base pricing of U.S. fed cattle: a hedonic approach - Rogers, Sheppard G. (Kansas State University, 2022)
The Livestock Mandatory Reporting Act of 1999 (LMR) was enacted by Congress more than two decades ago and marked one of the largest enhancements to livestock market transparency in recent history. In the 20 years since, cattle and beef markets hardly resemble the predominantly cash negotiated and undifferentiated product that characterized the industry in the early 2000s. Due in part to changing consumer preferences, formula-based marketing agreements have proliferated in the fed cattle industry. USDA began publishing formula base price information in August 2021. However, considerable variation in the types of cattle marketed on formula has raised questions about the level of base price transparency that can be gleaned from current USDA formula base price reports. This study employs about six years of formula base price transactions under LMR to estimate hedonic models assessing the capability of existing data to describe variation in formula base prices. Results suggest omitted variable bias in the models due to constraints of available data. We offer suggestions for improved data collection which we expect would make hedonic modeling of base prices a more efficient mechanism for reporting useful and interpretable market information.
Keywords: Market transparency; Formula base price; Price reporting; Hedonic models; Fed cattle